Demography and age heaping: Solving Ireland's post-famine digit preference puzzle - Eoin McLaughlin; Christopher L. Colvin; Stuart Henderson (European Historical Economics Society (EHES), 2022)
The quality of age reporting in Ireland worsened in the years after the Great Irish Famine (1845-1852), even as other measures of educational attainment improved. We show how demography partly accounts for this seemingly conflicting pattern. Specifically, we argue that a greater propensity to emigrate typified the youngest segment (23-32- year-olds) used in conventional indices of digit preference. Quantification of age heaping must therefore be interpreted in light of an older underlying population which is more likely to heap. We propose how age heaping indices can adjust for such demographic change by introducing age standardisation.
Keywords: N33; J10; 330; age heaping; human capital; demography